GAMIFIKASI, AR, DAN GEOGEBRA UNTUK KELAS MATEMATIKA YANG MENYENANGKAN: SYSTEMATIC LITERATURE REVIEW DAMPAK TEKNOLOGI IMERSIF TERHADAP JOYFUL LEARNING, MOTIVASI, DAN HIGHER-ORDER THINKING SKILLS - Adelia Putri; Riska Putri; Susanti Susanti; Edoy Saputra; Meria Ultra Gusteti; Khairul Azmi; Rahmatul Hayati (STKIP Pesisir Selatan, 2026)
Objective: The rapid development of digital technology has driven significant transformations in mathematics education, shifting instructional practices from conventional approaches toward more interactive, immersive, and meaningful learning experiences. This study aims to conduct a Systematic Literature Review (SLR) to examine the impacts of gamification, Augmented Reality (AR), and GeoGebra on mathematics learning, particularly in relation to joyful learning, learning motivation, and higher-order thinking skills (HOTS). Methods: This study employed a Systematic Literature Review by analyzing national and international peer-reviewed journal articles published between 2004 and 2025. The selected studies were systematically screened using predefined inclusion and exclusion criteria and analyzed through a thematic synthesis approach to identify key patterns, trends, and pedagogical implications. Results: The findings reveal that gamification consistently enhances students’ motivation and engagement through game elements such as challenges, rewards, and immediate feedback. Augmented Reality supports joyful and meaningful learning by enabling immersive experiences and facilitating spatial visualization of abstract mathematical concepts. Meanwhile, GeoGebra demonstrates strong potential in improving conceptual understanding and fostering higher-order thinking skills through dynamic visualization and exploratory learning activities.